A review of the aromatic genus Adenosma: Geographical distribution, traditional uses, phytochemistry and biological activities - Wang, Chen; Zhang, Hongxia; Liu, Qing; Qi, Jinfeng; Zhuang, Huifu; Gou, Yi; Wang, Hongbin; Wang, Yuhua (Journal of ethnopharmacology, 2021)
The strongly scented genus Adenosma R. Brown (Plantaginaceae) comprises between 26 and 29 species with mainly southeast Asian distributions. Several species are used traditionally, mostly in Asian countries, for medicinal purposes including the treatment of colds and tumors, as well as stomach, liver, and skin disorders. Some species are also used as insecticides and/or insect repellents against mosquitoes or fleas. Although the potential health benefits of Adenosma spp. are not yet well-known or well-studied in modern medicine, the aim of the present review is to provide a critical appraisal of the current state of knowledge regarding the geographical distribution, traditional uses, phytochemistry, phytochemicals and biological properties of Adenosma spp. Electronic databases (Web of Science, Science Direct, Google Scholar, Scifinder, Microsoft Academic, eFloras), Biodiversity Heritage Library (BHL), and the China National Knowledge Infrastructure (CNKI), were searched using the key words “Adenosma”, “毛麝香”, “大头陈”, “茵陈”, “nhân trần”, as well as the scientific names of the species, and a library search was also conducted for articles and books related to the subject published in English, Chinese or Vietnamese, as well as Ph.D. theses and M.Sc. dissertations published before April 2020. Adenosma spp. is traditionally used to treat gastrointestinal disorders, hepatitis, colds, and skin problems. Phenolic acids, flavonoids, and terpenoids constitute the main phytochemicals in these plants. Several evaluations based on bioassays have demonstrated biological activity for Adenosma spp., including antidiabetic, anticancer, and insecticidal activities; extracts and isolated compounds have also shown effective biological activity. However, current research has focused only on a few species, and on limited geographical regions, mainly in China and Vietnam. More and broader ethnopharmacological studies are therefore needed to provide further evidence of the health benefits of these plants. Adenosma spp. are plants rich in essential oils, particularly terpenoids, and the crude extracts have valuable bioactive properties. Certain lines of research based on cell lines and animal models show the potential value in different areas of health management. Further investigation into the traditional knowledge in southeast Asian and Pacific island regions, as well as the into the toxicity and identity of the bioactive compounds and their mechanisms of action is necessary.